High-strength and high-hardness aluminum alloy material as well as preparation method and application thereof
By optimizing the content of Si, Mg, Ti and other elements and heat treatment processes in the aluminum alloy brake caliper body, the problem of insufficient strength and hardness of the aluminum alloy brake caliper body is solved, and high strength, high hardness and stability are achieved, satisfying the Lightweight and high performance requirements for automotive brake systems.
Patent Information
- Application Number
- CN202411310218.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
AI Technical Summary
The strength, hardness and elongation of the existing aluminum alloy brake caliper body lead to poor braking effect, low reliability and unstable, making it difficult to meet the lightweight and high-performance needs of the automotive brake system.
Develop a high-strength, high-hard aluminum alloy material containing Si, Mg, Ti and other elements. Through specific ratios and heat treatment processes (such as T6 heat treatment), the metallographic structure of the material is optimized and the strength and hardness of the aluminum alloy are improved.
The high strength and hardness of the aluminum alloy brake caliper body are achieved, ensuring stability and reliability in extreme cases, meeting the requirements of braking effect, and improving the quality and production efficiency of castings.
Smart Images

Figure CN119177379A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of low-pressure casting, and in particular to a high-strength and high-hardness aluminum alloy material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the modern automobile industry, the performance requirements for automobile parts are also increasing. Especially in the braking system, the brake caliper body is a key component, and its material and manufacturing process have a vital impact on the safety and performance of the car. Traditional brake calipers are mostly made of cast iron. Although its strength and hardness meet the use requirements, it is heavy and is not conducive to the lightweight design of the car, thus affecting the fuel economy and power performance of the car.
[0003] In response to the urgent demand for lightweighting in the automotive industry, aluminum alloy materials have gradually attracted attention. Aluminum alloy has the advantages of low density, high strength, and good corrosion resistance, making it an ideal lightweight material. However, although the traditional gravity casting method is simple and easy to implement, it has low production efficiency, and the structural density and mechanical properties of the castings are often difficult to achieve the optimal level. The emergence of low-pressure casting technology has made it possible to manufacture aluminum alloys with high precision and high efficiency. Low-pressure casting can press molten metal into the mold at a relatively low pressure, effectively reducing casting defects such as pores and shrinkage cavities, and improving the quality and performance of castings. At the same time, low-pressure casting can also greatly improve production efficiency and reduce production costs.
[0004] For the special application of aluminum alloy brake caliper, it is required to have high strength and high hardness to ensure the braking effect, to ensure the stability and reliability of the caliper in extreme situations such as emergency braking, and at the same time, there is no high requirement for elongation. However, the direct application of gravity casting materials makes the strength and hardness fail to meet the use requirements. Therefore, it is of great significance to develop a high-strength and high-hardness aluminum alloy material suitable for low-pressure casting and explore its corresponding heat treatment method to improve the overall performance of aluminum alloy brake caliper.
[0005] Therefore, in response to the problems existing in the prior art, the designers of this case, relying on their many years of experience in this industry, actively researched and improved, and thus came up with the present invention of a high-strength and high-hardness aluminum alloy material and its preparation method and application. Summary of the invention
[0006] The first purpose of the present invention is to provide a high-strength and high-hardness aluminum alloy material in view of the defects in the prior art, such as the strength, hardness and elongation of the aluminum alloy brake caliper body are not sufficient to ensure the braking effect, the reliability is low, and there is great instability.
[0007] The second purpose of the present invention is to provide an application of a high-strength and high-hardness aluminum alloy material in view of the defects in the prior art, such as the strength, hardness and elongation of the aluminum alloy brake caliper body are not sufficient to ensure the braking effect, the reliability is low, and there is great instability.
[0008] The third purpose of the present invention is to provide a method for preparing high-strength and high-hardness aluminum alloy materials in view of the defects in the prior art, such as the strength, hardness and elongation of the aluminum alloy brake caliper body are not sufficient to ensure the braking effect, the reliability is low, and there is great instability.
[0009] To achieve the first purpose of the present invention, the present invention provides a high-strength and high-hardness aluminum alloy material, which comprises the following components by weight percentage: Si: 6.5-7.5wt%, Mg: 0.45-0.55wt%, Ti: 0.1-0.2wt%, Fe: wt%≤0.12wt%, Cu: wt%≤0.1wt%, Mn: wt%≤0.1wt%, Zn: wt%≤0.07wt%, Pb: wt%≤0.03wt%, P: wt%≤0.03wt%, Cr: wt%≤0.03wt%, Ni: wt%≤0.03wt%, Ca: wt%≤0.03wt%, Sn: wt%≤0.025wt%, Sr: 0.01-0.015wt%, and the balance is Al.
[0010] Optionally, the high-strength and high-hardness aluminum alloy material includes the following components by weight percentage: Si: 7.5wt%, Mg: 0.55wt%, Ti: 0.2wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al.
[0011] Optionally, the high-strength and high-hardness aluminum alloy material includes the following components by weight percentage: Si: 6.5wt%, Mg: 0.45wt%, Ti: 0.1wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al.
[0012] To achieve the second objective of the present invention, the present invention provides an application of a high-strength and high-hardness aluminum alloy material, wherein the high-strength and high-hardness aluminum alloy material is applied to low-pressure casting of a brake caliper body.
[0013] To achieve the third object of the present invention, the present invention provides a method for preparing a high-strength and high-hardness aluminum alloy material, the method for preparing the high-strength and high-hardness aluminum alloy material comprising:
[0014] Step S1: In terms of weight percentage, the ingredients are prepared in a ratio of Si: 6.5-7.5wt%, Mg: 0.45-0.55wt%, Ti: 0.1-0.2wt%, Fe: wt%≤0.12wt%, Cu: wt%≤0.1wt%, Mn: wt%≤0.1wt%, Zn: wt%≤0.07wt%, Pb: wt%≤0.03wt%, P: wt%≤0.03wt%, Cr: wt%≤0.03wt%, Ni: wt%≤0.03wt%, Ca: wt%≤0.03wt%, Sn: wt%≤0.025wt%, Sr: 0.01-0.015wt%, and the balance is Al;
[0015] Execute step S2: place the mixture of ingredients into a melting furnace, the melting temperature of the melting furnace is T≥750° C., and stir continuously with a graphite rod;
[0016] Execute step S3: after the mixture is melted in the melting furnace, add a slag removing agent to perform slag removing and refining;
[0017] Execute step S4: pour the aluminum alloy melt into the transfer furnace, close and seal the furnace mouth to ensure that the furnace is in a closed state, and then start the transfer furnace to make the temperature in the furnace reach 740° C. At the same time, fill Ar into the furnace to continuously stir the aluminum alloy melt to complete the degassing process;
[0018] Executing step S5: allowing the aluminum alloy melt to stand in a transfer furnace;
[0019] Execute step S6: The aluminum alloy melt after standing is made into aluminum ingots or transferred into a quantitative furnace for heat preservation in preparation for low-pressure casting.
[0020] Optionally, in step S2, the melting temperature T of the melting furnace satisfies 750°C≤T≤770°C, and a graphite rod is used for continuous stirring for not less than 20 minutes.
[0021] Optionally, in step S4, the aluminum alloy melt is poured into the converter, the furnace mouth is closed and sealed to ensure that the furnace is in a closed state, and then the converter is started so that the temperature in the furnace reaches 740°C. At the same time, Ar is filled into the furnace and the aluminum alloy melt is continuously stirred for 10 minutes.
[0022] Optionally, the method for preparing the high-strength and high-hardness aluminum alloy material further comprises:
[0023] Execute step S7: perform T6 heat treatment after low pressure casting.
[0024] Optionally, the T6 heat treatment parameters are: solution treatment at 540-550°C, heating time of 90-100min, and holding time of 360-380min; quenching at 25-35°C water temperature for 3-4min; aging temperature of 180-190°C, heating time of 90-100min, and holding time of 260-280min; and air cooling after exiting the furnace.
[0025] In summary, the present invention increases the content of main alloying elements Si, Mg, and Ti, adds or limits trace elements, optimizes the metallographic structure of the material, and performs T6 heat treatment to make the aluminum alloy brake caliper body have good strength and hardness, while the elongation meets the requirements, so that the prepared aluminum alloy brake caliper body has high strength and high hardness to ensure the braking effect, and ensure the stability and reliability of the caliper body under extreme conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The figure is a flow chart of the preparation method of the high-strength and high-hardness aluminum alloy material of the present invention;
[0027] Figure 2(a) to Figure 2(c) Shown is the sampling position of the brake caliper body tensile sample rod;
[0028] Figure 3 Shown is the sampling position of the brake caliper body hardness sample block;
[0029] Figure 4 The figure shows a 50 times magnified view of the metallographic phase diagram of the fifth embodiment of the present invention;
[0030] Figure 5 Shown is a 200-fold magnified view of the metallographic phase diagram of the fifth embodiment of the present invention. Specific embodiments
[0031] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] The high-strength and high-hardness aluminum alloy material of the present invention is applied to low-pressure casting of a brake caliper body. The high-strength and high-hardness aluminum alloy material comprises the following components by weight percentage:
[0033] Si: 6.5~7.5wt%, Mg: 0.45~0.55wt%, Ti: 0.1~0.2wt%, Fe: wt%≤0.12wt%, Cu: wt%≤0.1wt%, Mn: wt%≤0.1wt%, Zn: wt%≤0.07wt%, Pb: wt % ≤ 0.03wt%, P: wt% ≤ 0.03wt%, Cr: wt% ≤ 0.03wt%, Ni: wt% ≤ 0.03wt%, Ca: wt% ≤ 0.03wt%, Sn: wt% ≤ 0.025wt%, Sr: 0.01 to 0.015wt%, and the balance is Al.
[0034] See also Figure 1 , Figure 1 The flowchart of the method for preparing the high-strength and high-hardness aluminum alloy material of the present invention is shown. The method for preparing the high-strength and high-hardness aluminum alloy material comprises:
[0035] Step S1: In terms of weight percentage, the ingredients are prepared in a ratio of Si: 6.5-7.5wt%, Mg: 0.45-0.55wt%, Ti: 0.1-0.2wt%, Fe: wt%≤0.12wt%, Cu: wt%≤0.1wt%, Mn: wt%≤0.1wt%, Zn: wt%≤0.07wt%, Pb: wt%≤0.03wt%, P: wt%≤0.03wt%, Cr: wt%≤0.03wt%, Ni: wt%≤0.03wt%, Ca: wt%≤0.03wt%, Sn: wt%≤0.025wt%, Sr: 0.01-0.015wt%, and the balance is Al;
[0036] Execute step S2: place the mixture of ingredients into a melting furnace, the melting temperature of the melting furnace is T≥750° C., and stir continuously with a graphite rod;
[0037] Execute step S3: after the mixture is melted in the melting furnace, add a slag removing agent to perform slag removing and refining;
[0038] Execute step S4: pour the aluminum alloy melt into the transfer furnace, close and seal the furnace mouth to ensure that the furnace is in a closed state, and then start the transfer furnace to make the temperature in the furnace reach 740° C. At the same time, fill Ar into the furnace to continuously stir the aluminum alloy melt to complete the degassing process;
[0039] Executing step S5: allowing the aluminum alloy melt to stand in a transfer furnace;
[0040] Execute step S6: The aluminum alloy melt after standing is made into aluminum ingots or transferred into a quantitative furnace for heat preservation in preparation for low-pressure casting.
[0041] As a preferred embodiment, in step S2, the melting temperature T of the melting furnace satisfies 750°C≤T≤770°C, and a graphite rod is used to continuously stir for no less than 20 minutes to ensure the uniformity of the aluminum alloy melt and the consistency of the temperature. In step S4, the aluminum alloy melt is poured into the converter furnace, the furnace mouth is closed and sealed to ensure that the furnace is in a closed state, and then the converter furnace is started to make the temperature in the furnace reach 740°C, and Ar is filled into the furnace, and the aluminum alloy melt is continuously stirred for 10 minutes to complete the degassing process.
[0042] The high-strength and high-hardness aluminum alloy material of the present invention is applied to low-pressure casting of a brake caliper body. The preparation method of the high-strength and high-hardness aluminum alloy material further comprises:
[0043] Execute step S7: After the low-pressure casting is completed, perform T6 heat treatment with the following parameters: 540-550°C solid solution, heating time of 90-100min, holding time of 360-380min; 25-35°C water temperature quenching, time of 3-4min; aging temperature of 180-190°C, heating time of 90-100min, holding time of 260-280min; air cooling after exiting the furnace.
[0044] First embodiment
[0045] In the first embodiment, by way of non-limiting enumeration, the high-strength and high-hardness aluminum alloy material includes the following components, by weight percentage: Si: 7.5wt%, Mg: 0.5wt%, Ti: 0.15wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al.
[0046] The method for preparing the high-strength and high-hardness aluminum alloy material comprises:
[0047] Execute step S11: in terms of weight percentage, mix the ingredients in the following ratio: Si: 7.5wt%, Mg: 0.5wt%, Ti: 0.15wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al;
[0048] Execute step S12: place the mixture of ingredients into a melting furnace, the melting temperature of the melting furnace is 770° C., and stir continuously for 20 minutes using a graphite rod;
[0049] Executing step S13: after the mixture is melted in the melting furnace, adding a slag removing agent to perform slag removing and refining;
[0050] Execute step S14: pour the aluminum alloy melt into the converter, close and seal the furnace mouth to ensure that the furnace is in a closed state, then start the converter to make the furnace temperature reach 740°C, and fill Ar into the furnace, and continue to stir the aluminum alloy melt for 10 minutes to complete the degassing process;
[0051] Executing step S15: placing the aluminum alloy melt in the transfer furnace for 30 minutes;
[0052] Execute step S16: the aluminum alloy melt after standing is made into aluminum ingots or transferred into a quantitative furnace for heat preservation in preparation for low-pressure casting.
[0053] The high-strength and high-hardness aluminum alloy material of the present invention is applied to low-pressure casting of a brake caliper body. After the low-pressure casting is completed, T6 heat treatment is performed, and the parameters are: 540°C solid solution, heating time is 100 minutes, and insulation time is 360 minutes; 35°C water temperature quenching, time is 3 minutes; aging temperature is 180°C, heating time is 100 minutes, and insulation time is 260 minutes; air cooling after exiting the furnace.
[0054] Second embodiment
[0055] In the second embodiment, by way of non-limiting enumeration, the high-strength and high-hardness aluminum alloy material includes the following components, by weight percentage: Si: 6.5wt%, Mg: 0.5wt%, Ti: 0.15wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al.
[0056] The method for preparing the high-strength and high-hardness aluminum alloy material comprises:
[0057] Execute step S21: in terms of weight percentage, mix the ingredients in the following ratio: Si: 6.5wt%, Mg: 0.5wt%, Ti: 0.15wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al;
[0058] Execute step S22: place the mixture of ingredients into a melting furnace, the melting temperature of the melting furnace is 770° C., and stir continuously for 20 minutes using a graphite rod;
[0059] Execute step S23: after the mixture is melted in the melting furnace, add a slag removing agent to perform slag removing and refining;
[0060] Execute step S24: pour the aluminum alloy melt into the converter, close and seal the furnace mouth to ensure that the furnace is in a closed state, then start the converter to make the furnace temperature reach 740°C, and fill Ar into the furnace, and continue to stir the aluminum alloy melt for 10 minutes to complete the degassing process;
[0061] Executing step S25: placing the aluminum alloy melt in the transfer furnace for 30 minutes;
[0062] Execute step S26: The aluminum alloy melt after standing is made into aluminum ingots or transferred into a quantitative furnace for heat preservation in preparation for low-pressure casting.
[0063] The high-strength and high-hardness aluminum alloy material of the present invention is applied to low-pressure casting of a brake caliper body. After the low-pressure casting is completed, T6 heat treatment is performed, and the parameters are: 540°C solid solution, heating time is 100 minutes, and insulation time is 360 minutes; 35°C water temperature quenching, time is 3 minutes; aging temperature is 180°C, heating time is 100 minutes, and insulation time is 260 minutes; air cooling after exiting the furnace.
[0064] Third embodiment
[0065] In the third embodiment, by way of non-limiting enumeration, the high-strength and high-hardness aluminum alloy material includes the following components, by weight percentage: Si: 7.0wt%, Mg: 0.55wt%, Ti: 0.15wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al.
[0066] The method for preparing the high-strength and high-hardness aluminum alloy material comprises:
[0067] Execute step S31: in terms of weight percentage, mix the ingredients in the following ratio: Si: 7.0wt%, Mg: 0.55wt%, Ti: 0.15wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al;
[0068] Execute step S32: place the mixture of ingredients into a melting furnace, the melting temperature of the melting furnace is 770° C., and stir continuously for 20 minutes using a graphite rod;
[0069] Execute step S33: after the mixture is melted in the melting furnace, add a slag removing agent to perform slag removing and refining;
[0070] Execute step S34: pour the aluminum alloy melt into the converter, close and seal the furnace mouth to ensure that the furnace is in a closed state, then start the converter to make the furnace temperature reach 740°C, and fill Ar into the furnace, and continue to stir the aluminum alloy melt for 10 minutes to complete the degassing process;
[0071] Executing step S35: leaving the aluminum alloy melt in the transfer furnace for 30 minutes;
[0072] Execute step S36: make the aluminum alloy melt after standing still into aluminum ingots or transfer it into a quantitative furnace for heat preservation in preparation for low-pressure casting.
[0073] The high-strength and high-hardness aluminum alloy material of the present invention is applied to low-pressure casting of a brake caliper body. After the low-pressure casting is completed, T6 heat treatment is performed, and the parameters are: 540°C solid solution, heating time is 100 minutes, and insulation time is 360 minutes; 35°C water temperature quenching, time is 3 minutes; aging temperature is 180°C, heating time is 100 minutes, and insulation time is 260 minutes; air cooling after exiting the furnace.
[0074] Fourth embodiment
[0075] In the fourth embodiment, by way of non-limiting enumeration, the high-strength and high-hardness aluminum alloy material includes the following components, by weight percentage: Si: 7.0wt%, Mg: 0.45wt%, Ti: 0.15wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al.
[0076] The method for preparing the high-strength and high-hardness aluminum alloy material comprises:
[0077] Execute step S41: in terms of weight percentage, mix the ingredients in the following ratio: Si: 7.0wt%, Mg: 0.45wt%, Ti: 0.15wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al;
[0078] Execute step S42: place the mixture of ingredients into a melting furnace, the melting temperature of the melting furnace is 770° C., and stir continuously for 20 minutes using a graphite rod;
[0079] Execute step S43: after the mixture is melted in the melting furnace, add a slag removing agent to perform slag removing and refining;
[0080] Execute step S44: pour the aluminum alloy melt into the converter, close and seal the furnace mouth to ensure that the furnace is in a closed state, then start the converter to make the furnace temperature reach 740°C, and fill Ar into the furnace, and continue to stir the aluminum alloy melt for 10 minutes to complete the degassing process;
[0081] Executing step S45: leaving the aluminum alloy melt in the transfer furnace for 30 minutes;
[0082] Execute step S46: the aluminum alloy melt after standing is made into aluminum ingots or transferred into a quantitative furnace for heat preservation in preparation for low-pressure casting.
[0083] The high-strength and high-hardness aluminum alloy material of the present invention is applied to low-pressure casting of a brake caliper body. After the low-pressure casting is completed, T6 heat treatment is performed, and the parameters are: 540°C solid solution, heating time is 100 minutes, and insulation time is 360 minutes; 35°C water temperature quenching, time is 3 minutes; aging temperature is 180°C, heating time is 100 minutes, and insulation time is 260 minutes; air cooling after exiting the furnace.
[0084] Fifth embodiment
[0085] In the fifth embodiment, by way of non-limiting enumeration, the high-strength and high-hardness aluminum alloy material includes the following components, by weight percentage: Si: 7.0wt%, Mg: 0.5wt%, Ti: 0.2wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al.
[0086] The method for preparing the high-strength and high-hardness aluminum alloy material comprises:
[0087] Execute step S51: in terms of weight percentage, mix the ingredients in the following ratio: Si: 7.0wt%, Mg: 0.5wt%, Ti: 0.2wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al;
[0088] Execute step S52: place the mixture of ingredients into a melting furnace, the melting temperature of the melting furnace is 770° C., and stir continuously for 20 minutes using a graphite rod;
[0089] Execute step S53: after the mixture is melted in the melting furnace, add a slag removing agent to perform slag removing and refining;
[0090] Execute step S54: pour the aluminum alloy melt into the converter, close and seal the furnace mouth to ensure that the furnace is in a closed state, then start the converter to make the furnace temperature reach 740°C, and fill Ar into the furnace, and continue to stir the aluminum alloy melt for 10 minutes to complete the degassing process;
[0091] Executing step S55: leaving the aluminum alloy melt in the transfer furnace for 30 minutes;
[0092] Execute step S56: make the aluminum alloy melt after standing still into aluminum ingots or transfer it into a quantitative furnace for heat preservation in preparation for low-pressure casting.
[0093] The material is used for low-pressure casting of brake inlays, and after completion, T6 heat treatment is performed with the following parameters: 540°C solid solution, heating time of 100 min, holding time of 360 min; 35°C water temperature quenching for 3 min; aging temperature of 180°C, heating time of 100 min, holding time of 260 min; and air cooling after exiting the furnace.
[0094] Sixth embodiment
[0095] In the sixth embodiment, by way of non-limiting enumeration, the high-strength and high-hardness aluminum alloy material includes the following components, by weight percentage: Si: 7.0wt%, Mg: 0.5wt%, Ti: 0.1wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al.
[0096] The method for preparing the high-strength and high-hardness aluminum alloy material comprises:
[0097] Execute step S61: In terms of weight percentage, the ingredients are prepared in a ratio of Si: 7.0wt%, Mg: 0.5wt%, Ti: 0.1wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al;
[0098] Execute step S62: place the mixture of ingredients into a melting furnace, the melting temperature of the melting furnace is 770° C., and stir continuously for 20 minutes using a graphite rod;
[0099] Execute step S63: after the mixture is melted in the melting furnace, add a slag removing agent to perform slag removing and refining;
[0100] Execute step S64: pour the aluminum alloy melt into the transfer furnace, close and seal the furnace mouth to ensure that the furnace is in a closed state, then start the transfer furnace to make the furnace temperature reach 740°C, and fill Ar into the furnace, and continue to stir the aluminum alloy melt for 10 minutes to complete the degassing process;
[0101] Executing step S65: leaving the aluminum alloy melt in the transfer furnace for 30 minutes;
[0102] Execute step S66: the aluminum alloy melt after standing is made into aluminum ingots or transferred into a quantitative furnace for heat preservation in preparation for low-pressure casting.
[0103] The high-strength and high-hardness aluminum alloy material of the present invention is applied to low-pressure casting of a brake caliper body. After the low-pressure casting is completed, T6 heat treatment is performed, and the parameters are: 540°C solid solution, heating time is 100 minutes, and insulation time is 360 minutes; 35°C water temperature quenching, time is 3 minutes; aging temperature is 180°C, heating time is 100 minutes, and insulation time is 260 minutes; air cooling after exiting the furnace.
[0104] In order to more intuitively disclose the technical solution of the present invention and highlight the beneficial effects of the present invention, the component selection of the high-strength and high-hardness aluminum alloy material of the present invention is now described in combination with the mechanical property test results.
[0105] Si element: Si is the main component to improve the fluidity of aluminum alloy. As the Si content increases, the melting point of aluminum alloy decreases and the fluidity increases, making it easier for aluminum alloy to fill the mold and obtain better casting quality. At the same time, increasing the Si content can improve the strength and hardness of aluminum alloy, but too high a silicon content will cause a significant decrease in the elongation of hypereutectic aluminum alloy.
[0106] Mg element: It can significantly improve the strength and hardness of aluminum alloys, but it will also reduce the elongation. The formation of Mg2Si strengthening phase in aluminum alloys is particularly important for heat-treated parts.
[0107] Ti element: It is a commonly used additive element in aluminum alloys, added in the form of Al-Ti or Al-Ti-B master alloys. Titanium and aluminum form TiAl2 phase, which becomes the non-spontaneous core during crystallization, plays a role in refining grains, and helps to improve the strength and elongation of the alloy.
[0108] Fe element: It exists in the form of Al9Fe2Si2 in aluminum alloy, which is a coarse, needle-shaped brittle phase. Too much Fe will split the matrix and significantly reduce the mechanical properties. However, an appropriate amount of Fe content (such as 0.6%-1.3%) can avoid mold sticking.
[0109] Cu element: When the temperature is 548℃, the solubility of copper in aluminum should be 5.65%, which drops to about 0.2% at room temperature. The right amount of copper content can significantly improve the strength and hardness of aluminum alloys, however, too high a copper content may lead to reduced plasticity and toughness of aluminum alloys.
[0110] Mn element: It can prevent the recrystallization process of aluminum alloy, increase the recrystallization temperature, and refine the recrystallized grains. Mn plays a role in solid solution strengthening during heat treatment of aluminum alloy. Mn forms (Fe, Mn) Al6 with iron to reduce the harmful effects of iron. However, when the Mn content is too high, it will cause segregation.
[0111] Zn element: It mainly plays a strengthening role in aluminum alloys and can form a strengthening phase with other elements.
[0112] Pb and Sn elements: can improve the cutting performance of aluminum alloys.
[0113] Cr, Ni, Ca, and Sr: These elements exist in trace amounts in aluminum alloys. Cr and Ni can improve corrosion resistance and strength, and Ca and Sr may be used for modification to improve the casting properties of aluminum alloys.
[0114] The present invention optimizes the metallographic structure of the material by adjusting the content of the main alloy elements Si, Mg, and Ti, adding or limiting trace elements, and using a specific T6 heat treatment process to make the low-pressure cast aluminum alloy clamp body have excellent strength, hardness, and suitable elongation. The T6 is a heat treatment process, that is, a state of artificial aging after solution heat treatment. This process can be used for deformed aluminum alloys and cast aluminum alloys.
[0115] See also Figure 2(a) to Figure 2(c) , Figure 3 , Figure 2(a) to Figure 2(c) The sample positions of the stretching sample rod of the brake caliper body are shown. The sample positions of the stretching sample rod of the brake caliper body 1 are 16. Figure 3 The figure shows the sampling positions of the hardness sample block of the brake caliper body. The sampling positions of the hardness sample block of the brake caliper body 1 are 2. Table 1 is a performance test table of the brake caliper body of the first embodiment to the sixth embodiment.
[0116] Table 1 Mechanical properties of low pressure cast high strength and high hardness aluminum alloy materials of Examples 1-6
[0117] Serial number Yield strength (MPa) Tensile strength(MPa) Elongation(%) Hardness(HBW) First embodiment 296 337 1.3 121 Second embodiment 278 316 2.1 113 Third embodiment 291 332 1.9 126 Fourth embodiment 286 326 2.4 124 Fifth embodiment 292 333 2.6 127 Sixth embodiment 289 327 2.4 126
[0118] See also Figure 4 , Figure 5 , Figure 4 Shown is a 50-fold magnified view of the metallographic phase diagram of the fifth embodiment of the present invention. Figure 5 The figure shows a 200-fold magnified view of the metallographic diagram of the fifth embodiment of the present invention. As a person skilled in the art can see from the figure, in the metallographic structure of low-pressure casting of conventional aluminum alloy materials, the grains are coarse and the Si phase is distributed in a coarse lath shape. The high-strength and high-hardness low-pressure casting aluminum alloy of the present invention has a refined Si phase and a fine, uniform and dense overall metallographic structure, which shows that the aluminum alloy has good strength and hardness.
[0119] In summary, the present invention increases the content of main alloying elements Si, Mg, and Ti, adds or limits trace elements, optimizes the metallographic structure of the material, and performs T6 heat treatment to make the aluminum alloy brake caliper body have good strength and hardness, while the elongation meets the requirements, so that the prepared aluminum alloy brake caliper body has high strength and high hardness to ensure the braking effect, and ensure the stability and reliability of the caliper body under extreme conditions.
[0120] Those skilled in the art will appreciate that various modifications and variations may be made to the present invention without departing from the spirit or scope of the present invention. Therefore, if any modification or variation falls within the scope of protection of the appended claims and equivalents, it is considered that the present invention covers these modifications and variations.
Claims
1. A high-strength and high-hardness aluminum alloy material, characterized in that: The high-strength and high-hardness aluminum alloy material comprises the following components by weight percentage: Si: 6.5~7.5wt%, Mg: 0.45~0.55wt%, Ti: 0.1~0.2wt%, Fe: wt%≤0.12wt%, Cu: wt%≤0.1wt%, Mn: wt%≤0.1wt%, Zn: wt%≤0.07wt%, Pb: wt % ≤ 0.03wt%, P: wt% ≤ 0.03wt%, Cr: wt% ≤ 0.03wt%, Ni: wt% ≤ 0.03wt%, Ca: wt% ≤ 0.03wt%, Sn: wt% ≤ 0.025wt%, Sr: 0.01 to 0.015wt%, and the balance is Al.
2. The high-strength and high-hardness aluminum alloy material according to claim 1, characterized in that: The high-strength and high-hardness aluminum alloy material comprises the following components by weight percentage: Si: 7.5wt%, Mg: 0.55wt%, Ti: 0.2wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al.
3. The high-strength and high-hardness aluminum alloy material according to claim 1, characterized in that: The high-strength and high-hardness aluminum alloy material comprises the following components by weight percentage: Si: 6.5wt%, Mg: 0.45wt%, Ti: 0.1wt%, Fe: 0.12wt%, Cu: 0.1wt%, Mn: 0.1wt%, Zn: 0.07wt%, Pb: 0.03wt%, P: 0.03wt%, Cr: 0.03wt%, Ni: 0.03wt%, Ca: 0.03wt%, Sn: 0.025wt%, Sr: 0.015wt%, and the balance is Al.
4. The high-strength and high-hardness aluminum alloy material according to any one of claims 1 to 3, characterized in that: The high-strength and high-hardness aluminum alloy material is applied to low-pressure casting of a brake caliper body.
5. A method for preparing the high-strength and high-hardness aluminum alloy material according to any one of claims 1 to 3, characterized in that: The method for preparing the high-strength and high-hardness aluminum alloy material comprises: Step S1: In terms of weight percentage, the ingredients are prepared in a ratio of Si: 6.5-7.5wt%, Mg: 0.45-0.55wt%, Ti: 0.1-0.2wt%, Fe: wt%≤0.12wt%, Cu: wt%≤0.1wt%, Mn: wt%≤0.1wt%, Zn: wt%≤0.07wt%, Pb: wt%≤0.03wt%, P: wt%≤0.03wt%, Cr: wt%≤0.03wt%, Ni: wt%≤0.03wt%, Ca: wt%≤0.03wt%, Sn: wt%≤0.025wt%, Sr: 0.01-0.015wt%, and the balance is Al; Execute step S2: place the mixture of ingredients into a melting furnace, the melting temperature of the melting furnace is T≥750° C., and stir continuously with a graphite rod; Execute step S3: after the mixture is melted in the melting furnace, add a slag removing agent to perform slag removing and refining; Execute step S4: pour the aluminum alloy melt into the transfer furnace, close and seal the furnace mouth to ensure that the furnace is in a closed state, and then start the transfer furnace to make the temperature in the furnace reach 740° C. At the same time, fill Ar into the furnace to continuously stir the aluminum alloy melt to complete the degassing process; Executing step S5: allowing the aluminum alloy melt to stand in a transfer furnace; Execute step S6: The aluminum alloy melt after standing is made into aluminum ingots or transferred into a quantitative furnace for heat preservation in preparation for low-pressure casting.
6. The method for preparing the high-strength and high-hardness aluminum alloy material according to claim 5, characterized in that: In step S2, the melting temperature T of the melting furnace satisfies 750°C≤T≤770°C, and a graphite rod is used for continuous stirring for not less than 20 minutes.
7. The method for preparing the high-strength and high-hardness aluminum alloy material according to claim 5, characterized in that: In step S4, the aluminum alloy melt is poured into the converter, and the furnace mouth is closed and sealed to ensure that the furnace is in a closed state. The converter is then started so that the temperature in the furnace reaches 740°C. At the same time, Ar is filled into the furnace, and the aluminum alloy melt is continuously stirred for 10 minutes.
8. The method for preparing the high-strength and high-hardness aluminum alloy material according to claim 5, characterized in that: The method for preparing the high-strength and high-hardness aluminum alloy material further comprises: Execute step S7: perform T6 heat treatment after low pressure casting.
9. The method for preparing the high-strength and high-hardness aluminum alloy material according to claim 8, characterized in that: The T6 heat treatment parameters are: solution treatment at 540-550°C, heating time of 90-100min, and holding time of 360-380min; quenching at 25-35°C water temperature for 3-4min; aging temperature of 180-190°C, heating time of 90-100min, and holding time of 260-280min; and air cooling after exiting the furnace.
